Political parties' accountability to the public in Nepal: What factors affect it? - Anil Kumar Gupta; Hari P. Dhungana; Bishnu Prasad Lamsal (Heliyon)
Political accountability is essential for maintaining trust and transparency in governance. However, the factors that influence political parties' accountability remain underexplored in Nepal. This paper examines the factors influencing citizens' perceptions of political parties' accountability in Nepal, utilizing data from the National Governance Survey 2017/18 (N = 4191). A four-stage multiple cluster sampling technique was used to randomly select respondents from 43 out of 77 districts in Nepal. Data were collected between December 2017 and March 2018. Results from logistic regression analysis indicate that citizens' perceptions of political parties' honesty, transparency, adherence to rules, and corruption control significantly impact political parties' accountability. While citizen engagement in political discussions was positively associated with political parties' accountability, this factor did not demonstrate statistical significance. These findings highlight the importance of honesty, transparency, rule of law, and anti-corruption measures in fostering political parties' accountability. This study contributes to the literature on democratic governance and offers practical insights for authorities seeking to strengthen accountable political institutions in Nepal. The insights of this paper provide a roadmap for political parties to prioritize ethical conduct, proactive information sharing, regulatory compliance, and anti-graft efforts to build public trust and accountability.